The use of palm leaf fibres as reinforcements in composites - (:unkn) unknown (WOODHEAD PUBL LTD, 2015)
Firstly, the importance of palm leaf fibres in different industries, and as a potential alternative to synthetic fibres, is outlined. The cultivation and uses of palm leaf fibres are then explored before a description of their various properties is outlined. Different methods of surface modification are explained before discussing how palm leaf fibres can be used as reinforcements in polymer nanocomposites.
Keywords: palm leaf fibres; cellulose; natural fibres; mechanical properties; surface modification; composite; adhesion; nanocomposites